1979
DOI: 10.1126/science.758682
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Epileptic Seizures Through Operant Conditioning of Central Nervous System Activity: Procedural Variables

Abstract: Operant conditioning of the sensorimotor rhythm of the human electroencephalogram with time-outs contingent on epileptiform activity reduces epileptic seizure rates in patients whose seizures are not well controlled by medication. A comparison of this procedure with time-out training alone demonstrates that operant conditioning of the sensorimotor rhythm is neither necessary nor sufficient for seizure reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For instance, Cott, Pavloski, and Black (1979) reported that 3 months of SMR training was associated with significantly reduced seizure incident in five out of seven patients who had previously suffered from very poorly controlled seizures. These high success rates of SMR training were further confirmed in investigations that employed more elaborate control conditions, such as non-contingent, or random feedback (Finley, Smith, & Etherton, 1975;Kuhlman & Allison, 1978;Quy, Forrest, & Hutt, 1979;Wyler, Robbins, & Dodrill, 1976).…”
Section: Clinical Findings With Epilepsymentioning
confidence: 98%
“…For instance, Cott, Pavloski, and Black (1979) reported that 3 months of SMR training was associated with significantly reduced seizure incident in five out of seven patients who had previously suffered from very poorly controlled seizures. These high success rates of SMR training were further confirmed in investigations that employed more elaborate control conditions, such as non-contingent, or random feedback (Finley, Smith, & Etherton, 1975;Kuhlman & Allison, 1978;Quy, Forrest, & Hutt, 1979;Wyler, Robbins, & Dodrill, 1976).…”
Section: Clinical Findings With Epilepsymentioning
confidence: 98%
“…Cott et al 11 studied 3 mentally disabled individuals with seizure disorders and provided them with 8–12 Hz occipital EEG biofeedback training. All 3 participants experienced decreases in some of their seizure activity; however, their inability to increase 8–12 Hz activity brought into question the effectiveness of feedback stimuli used as reinforcers with these individuals.…”
Section: Appendix: Review Of Literaturementioning
confidence: 99%
“…The results of the study indicate that changes in procedures will be necessary for future studies to determine if 8–12 Hz occipital EEG training is effective in reducing epileptic seizures. 11…”
Section: Appendix: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A more recent meta-analysis with strict inclusion criteria reviewed 10 studies from 1970 through 2005, each providing detailed information on patient selection, utilizing SMR-or SCP-based biofeedback, and reporting individual subjects' pre-and post-treatment seizure data [54]. Nine studies were of SMR in participants with refractory epilepsy, with withinsubject designs [55][56][57][58][59][60][61][62][63], while one study utilized SCP-based biofeedback [51]. All studies reported an overall mean decrease in seizure frequency following treatment, and 74% of all participants reported fewer weekly seizures in response to EEG biofeedback.…”
Section: Biofeedbackmentioning
confidence: 99%